2012
DOI: 10.1038/nchembio.765
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterols are allosteric activators of the oncoprotein Smoothened

Abstract: Oxysterols are a class of endogenous signaling molecules that can activate the Hedgehog pathway, which plays critical roles in development, regeneration and cancer. However, it has been unclear how oxysterols influence Hedgehog signaling, including whether their effects are mediated through a protein target or indirectly through effects on membrane properties. To answer this question, we synthesized the enantiomer and an epimer of the most potent oxysterol, 20(S)-hydroxycholesterol. Using these molecules, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
291
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(315 citation statements)
references
References 50 publications
21
291
0
3
Order By: Relevance
“…Curiously, despite its inhibition of 20(S)-OHC activation, DHCEO does not completely block the synergy between 20(S)-OHC and SAG (39). We thus found that addition of 20(S)-OHC both increased the potency of SAG (reduced its EC 50 ) and increased the maximum level of pathway activation achieved (Fig.…”
Section: Ergosterol Endoperoxide Isolated From Chlamydomonas Reinhardtiimentioning
confidence: 54%
See 1 more Smart Citation
“…Curiously, despite its inhibition of 20(S)-OHC activation, DHCEO does not completely block the synergy between 20(S)-OHC and SAG (39). We thus found that addition of 20(S)-OHC both increased the potency of SAG (reduced its EC 50 ) and increased the maximum level of pathway activation achieved (Fig.…”
Section: Ergosterol Endoperoxide Isolated From Chlamydomonas Reinhardtiimentioning
confidence: 54%
“…5A). DHCEO also inhibited two other CRD agonists, 7-keto-27-hydroxycholesterol (7KCh-27OH) (18) and 20(S)-yne (39), in an apparently noncompetitive manner (Fig. 5 B and C).…”
Section: Ergosterol Endoperoxide Isolated From Chlamydomonas Reinhardtiimentioning
confidence: 99%
“…lipid. Psy and its enantiomer altered bilayers of liposomes, making them more water permeable and allowing the vesicles to expand their volume as the added sphingolipid partitioned into the membrane ( 21,36 ). It is clear that psy and ent-psy alter the integrity of model membrane systems.…”
Section: Drm Microdomain Compositionmentioning
confidence: 99%
“…Hydroxysterols have been shown to stimulate Smo activity [9,10,11] by binding to its Nterminal domain [11,12,13]. Although MS/MS analysis detected hydroxysterols in fractions 33-peer-reviewed) is the author/funder.…”
Section: Spectrometry (Ms/ms) and Thin Layer Chromatography (Tlc) Msmentioning
confidence: 99%